Effective Region of Multi-connected Air-conditioner (Heat pump) System - Shi Wenxing; Shao Shuangquan; Yan Qisen (Zhileng xuebao)
The "effective region" of multi-connected air-conditioner(heat pump) system was proposed,which includes the safety region,the efficiency region and the adjustability region.Based on the system simulation model,the factors that influence the three effective regions were investigated.Moreover,the quantitative regions are presented for the system charged with HCFC22.